A method for preparing a sulfidation-type hydrodemetallization catalyst

By introducing multifunctional complexing agent and microwave drying technology into hydrodemetalization catalysts, vulcanization catalysts with high efficiency activity and long life are prepared, which solves the problems of catalyst bed scaling and short service life, and is suitable for high sulfur Hydrotation of high nitrogen and high metal content oils.

CN116139895BActive Publication Date: 2024-12-17CHINA NAT OFFSHORE OIL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211729401.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-31
Publication Date
2024-12-17
Estimated Expiration
2042-12-31

AI Technical Summary

Technical Problem

During use, existing hydrodemetalization catalysts are prone to fouling and blocking the catalyst bed due to impurity deposition, and are forced to stop work due to excessive pressure drop. They have a short service life, making it difficult to effectively deal with the inferior quality of high sulfur, high nitrogen and high metal content. Oil products.

Method used

The vulcanized hydrodemetallic catalyst is prepared with a multifunctional complexing agent combined with hot impregnation, phthalidite powder, phthalidite filter cake, ultrasonic dispersion and microwave drying treatment at different frequencies. 、协同性好、催化活性强、孔容大、比表面积高和强度高的特点。

Benefits of technology

This method provides an efficient and simple catalyst preparation method, which can effectively solve the problem of scaling and blocking of the catalyst bed, extend the service life of the hydrogenation catalyst, and significantly improve the processing capacity of high sulfur, high nitrogen and high metal content oils.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention discloses a method for preparing a sulfur-based hydrodemetallization catalyst. The method includes: first, mixing and heating ammonium dithiocarbamate, nickel salt and / or cobalt salt, citric acid, ethylene glycol, and deionized water; then adding ammonium tetrathiomolybdate and / or ammonium tetrathiotungstate; and mixing the resulting sulfur-containing composite active metal precursor impregnation solution with boehmite powder, boehmite filter cake, zinc phosphate, ammonium borate, starch, alumina sol, silica sol, magnesium carbonate, a pore-forming agent, and a microwave sensitizer at 50℃~90℃. After ultrasonic dispersion, slurrying, kneading, and extrusion molding, the mixture is microwave-dried under nitrogen protection at radiation frequencies of 840MHz and 2450MHz to obtain the sulfur-based hydrodemetallization catalyst. The sulfur-based hydrodemetallization catalyst prepared by this invention combines the functions of a conventional protective agent with excellent hydrodemetallization activity, and can be widely used in oil hydrotreating, especially in the hydrotreating process of inferior oils with high sulfur, high nitrogen, and high metal content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a sulfidation type hydrodemetallization catalyst. Background Art

[0002] As the quality of crude oil deteriorates, the content of impurities such as colloid, asphaltene and organometallic compounds in crude oil increases. The presence of these impurities can easily cause the catalyst activity to drop rapidly and even become inactivated. An effective way to solve this problem is to load a protective agent with hydrogenation activity on the upper part of the hydrogenation catalyst bed. Hydrodemetallization catalysts with larger pore volume and pore diameter have strong metal and carbon tolerance, which can protect the downstream hydrogenation main agent and extend the service life of the main agent.

[0003] Examples of hydrodemetallization catalysts and their preparation in the prior art include:

[0004] CN200610113493.5 discloses a hydrogenation protective agent and its preparation, the protective agent contains one or more porous heat-resistant inorganic oxides, characterized in that the total pore volume of the protective agent is 0.3-1.5 mm / g, wherein the protective agent contains millimeter-level macropores, the diameter of the millimeter-level macropores is 0.1-1.5 microns, and the pore volume of the millimeter-level macropores is 0.05-0.7 ml / g. The preparation method of the hydrogenation protective agent comprises mixing, molding, drying and roasting one or more porous heat-resistant inorganic oxides and / or precursors of porous heat-resistant inorganic oxides with at least one organic matter, wherein the organic compound is a solid particle with a melting point between 30 and 200°C, a particle size of 0.3-2.5 mm and insoluble in water.

[0005] CN201010220850.4 discloses a method for preparing a hydroprocessing protective agent. In the method, an alumina carrier is prepared by kneading two different pseudo-boehmite dry rubber powders, and then loaded with active metals; the first pseudo-boehmite has a relatively small crystallinity and a large pore volume, and can provide pores with a pore diameter of 30nm to 100nm, and the second pseudo-boehmite has a relatively high crystallinity and can provide micron-level pores. Because of its high acidity index, it presents an extremely hard block after drying, and after being crushed, 100% of it passes through 50 mesh, which can not only increase the number of micron-level pores, but also improve the strength of the catalyst carrier. By adjusting the mixing ratio between the two, a hydroprocessing protective agent with high strength, large bulk density, large pore volume and low wear rate can be prepared.

[0006] CN98111379.6 discloses a hydrodemetallization catalyst and its preparation method. The catalyst carrier has a super large pore size, a bimodal pore size of 0.1 to 30 μm, a catalyst pore volume of 0.1 to 0.8 mL / g, and a specific surface area of ​​0.1 to 20 m 2 / g, containing 6.65m% to 20.0m% of VIB group metal elements and / or 8.71% to 26.13m% of group VIII metal elements. The preparation method is to prepare an alumina carrier by a particle stacking method, and then impregnate it with equal amounts of a molybdenum-containing solution and a nickel-containing solution, and the impregnated catalyst is dried at 100 to 120°C for 2 to 5h, and calcined at 500 to 550°C for 2 to 5h.

[0007] CN00110019.X discloses a hydrogenation active protective agent and its preparation method. The carrier used in the protective agent contains both γ-alumina and δ-alumina. The protective agent contains 3-22m% of VIB group metal oxide and 0.5-5m% of VIII group metal oxide, 0-2m% of IA group metal oxide, 0-3m% of phosphorus, and a specific surface area of ​​100-250m 2 / g. Pore volume 0.4~0.8mL / g.

[0008] CN200910206230.2 discloses a residual oil hydrogenation demetallization catalyst and its application. The catalyst has large pore volume, large pore diameter, high porosity, reasonable pore distribution, large surface pore opening, good pore penetration, and contains more than 36% of pores above 1000nm. Especially when used in the residual oil fixed bed hydrogenation method, the demetallized metal can be uniformly precipitated in the entire catalyst bed, and the impurities vanadium and calcium can be precipitated inside the pores, thereby improving the utilization rate of the pores and maintaining long-term operation.

[0009] The above-mentioned prior art provides various solutions to the problems in the use of hydrodemetallization catalysts. It is not difficult to see that the pore properties of the carrier (including pore volume, pore size, pore distribution and other properties) directly determine the performance of such catalysts. Summary of the invention

[0010] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art. The method of the present invention introduces a multifunctional complexing agent, combines hot impregnation, pseudo-boehmite powder (60-70wt% on a dry basis), pseudo-boehmite filter cake (20-25wt% on a dry basis), ultrasonic dispersion and microwave drying treatment of different frequencies under nitrogen protection, to provide a method for preparing a sulfided hydrodemetallization catalyst with high efficiency and simplicity, uniform dispersion of active metals, good synergy of different active metals, high effective utilization rate of active metals, good catalytic activity, large pore volume, high specific surface area, high strength and strong hydrodemetallization ability.

[0011] The present invention provides a method for preparing a sulfided hydrodemetallization catalyst, the preparation method comprising:

[0012] A preparation method of a sulfurized hydrodemetallization catalyst comprises: firstly mixing ammonium dithiocarbamate, nickel salt and / or cobalt salt, citric acid, ethylene glycol and a certain amount of deionized water, heating and stirring, then adding ammonium tetrathiomolybdate and / or ammonium tetrathiotungstate, and mixing the obtained sulfur-containing composite active metal precursor impregnation liquid with pseudo-boehmite powder (60-70wt% on dry basis), pseudo-boehmite filter cake (20-25wt% on dry basis), zinc phosphate, ammonium borate, starch, aluminum sol, silica sol, magnesium carbonate, pore-forming agent at a temperature of 50°C to 90°C. The invention relates to a method for preparing a sulfide-type hydrodemetallization catalyst. The method comprises mixing a sulfide-type hydrodemetallization catalyst, a microwave sensitizer and a dispersant, and then performing ultrasonic dispersion, beating, kneading and extrusion. The sulfide-type hydrodemetallization catalyst is first dried with a microwave having a radiation frequency of 840 MHz and a microwave drying temperature of 100 to 120° C., and then dried with a microwave having a radiation frequency of 2450 MHz and a microwave drying temperature of 350 to 600° C. under nitrogen protection. The molar amount of the ammonium dithiocarbamate used is 50% to 300% of the molar amount of the nickel salt and / or the cobalt salt, preferably 100% to 150%.

[0013] The nickel salt and / or cobalt salt is selected from one or more of basic carbonate, nitrate and acetate, preferably basic carbonate.

[0014] The pore-forming agent is preferably one or more of ammonium carbonate, ammonium bicarbonate, urea, ammonium oxalate, polymethyl methacrylate and polystyrene microspheres, and the amount used is 1wt% to 20wt% of the weight of the carrier component.

[0015] The microwave sensitizer is preferably one or more of Fenton's reagent, activated carbon, graphite, conductive carbon black, semi-conductive carbon black and carbon fiber sensitizer.

[0016] The ultrasonic time is 5 to 30 minutes.

[0017] The 840 MHz microwave drying time is 10 to 30 minutes; the 2450 MHz microwave drying time is 20 to 120 minutes.

[0018] The sulfided hydrodemetallization catalyst has a total nickel and / or cobalt content of 0.5wt% to 5wt% and a total molybdenum and / or tungsten content of 1wt% to 15wt% based on the weight of the final catalyst.

[0019] The method of the present invention provides a method for preparing a sulfurized hydrodemetallization catalyst with high efficiency and simplicity, uniform active metal dispersion, good synergy between different active metals, high effective utilization rate of active metals, good catalytic activity, large pore volume, high specific surface area, high strength and good hydrodemetallization performance by introducing a multifunctional complexing agent, combining hot impregnation, pseudo-boehmite powder (60-70wt% on dry basis), pseudo-boehmite filter cake (20-25wt% on dry basis), ultrasonic dispersion and microwave drying treatment of different frequencies under nitrogen protection. Compared with the hydrodemetallization catalyst provided by the prior art, the hydrodemetallization catalyst provided by the present invention has excellent hydrodemetallization activity while having the function of a conventional protective agent, can be widely used in the hydroprocessing process of oil products, is particularly suitable as a hydrodemetallization catalyst for inferior oil products with high sulfur, high nitrogen and high metal content, can effectively solve the problems of fouling, clogging and forced shutdown of catalyst bed of industrial hydrogenation device due to excessive pressure drop, and prolongs the service life of the hydrodemetallization catalyst. DETAILED DESCRIPTION

[0020] The technical features of the present invention are described in detail below with specific embodiments, but the embodiments do not limit the protection scope of the present invention.

[0021] The specific preparation steps of the present invention are as follows: first, ammonium dithiocarbamate, nickel salt and / or cobalt salt, citric acid, ethylene glycol and a certain amount of deionized water are mixed, heated and stirred, then ammonium tetrathiomolybdate and / or ammonium tetrathiotungstate are added, the obtained sulfur-containing composite active metal precursor impregnation solution is mixed with pseudo-boehmite powder (60-70wt% on a dry basis), pseudo-boehmite filter cake (20-25wt% on a dry basis), zinc phosphate, ammonium borate, starch, aluminum sol, silica sol, magnesium carbonate, two pore-forming agents and a microwave sensitizer at a temperature of 50°C to 90°C, then ultrasonically dispersed, beaten, kneaded, extruded and formed, and then, under nitrogen protection, first dried with a microwave having a radiation frequency of 840MHz and a microwave drying temperature of 100°C to 120°C, and then dried with a microwave having a radiation frequency of 2450MHz and a microwave drying temperature of 350°C to 600°C, to obtain a sulfurized hydrogenation demetallization catalyst.

[0022] Embodiment 1:

[0023] 4 g of ammonium dithiocarbamate, 2 g of basic nickel carbonate, 2 g of citric acid, 1 g of ethylene glycol and 40 g of deionized water were mixed, heated and stirred at 90° C., and then 10 g of ammonium tetrathiomolybdate was added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed at 90° C. with 60 g of pseudo-boehmite powder (68 wt% on dry basis), 40 g of pseudo-boehmite filter cake (20 wt% on dry basis), 0.5 g of zinc phosphate, 0.5 g of ammonium borate, 1 g of starch, 1 g of aluminum sol, 1 g of Silica sol, 0.5 g of magnesium carbonate, 5 g of ammonium bicarbonate, 10 g of urea and 0.5 g of activated carbon were mixed, and then ultrasonically dispersed for 5 minutes, beaten, kneaded, and extruded into strips. Then, under nitrogen protection, the mixture was first dried with microwaves having a radiation frequency of 840 MHz, a microwave drying temperature of 100°C, and a drying time of 10 minutes, and then dried with microwaves having a radiation frequency of 2450 MHz, a microwave drying temperature of 450°C, and a drying time of 30 minutes to obtain a sulfided hydrodemetallization catalyst 1.

[0024] Embodiment 2:

[0025] 1 gram of ammonium dithiocarbamate, 2 grams of nickel nitrate, 1 gram of nickel acetate, 1 gram of citric acid, 1 gram of ethylene glycol and 40 grams of deionized water were mixed, heated and stirred at 80°C, and then 10 grams of ammonium tetrathiotungstate were added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed with 80 grams of pseudo-boehmite powder (65wt% on dry basis), 20 grams of pseudo-boehmite filter cake (22wt% on dry basis), 0.5 grams of zinc phosphate, 0.5 grams of ammonium borate, 1 gram of starch, 1 gram of aluminum sol, 1 gram of silica sol, 0.5 gram of magnesium carbonate, 10 grams of ammonium carbonate, 3 grams of ammonium oxalate and 1 gram of Fenton's reagent were mixed, and then ultrasonically dispersed for 30 minutes, beaten, kneaded, and extruded into strips. Then, under nitrogen protection, they were first dried with microwaves at a radiation frequency of 840 MHz, a microwave drying temperature of 110°C, and a drying time of 15 minutes, and then dried with microwaves at a radiation frequency of 2450 MHz, a microwave drying temperature of 600°C, and a drying time of 20 minutes to obtain a sulfurized hydrodemetallization catalyst 2.

[0026] Embodiment 3:

[0027] 1.5 g of ammonium dithiocarbamate, 1.5 g of nickel nitrate, 1.3 g of nickel acetate, 1 g of citric acid, 1 g of ethylene glycol and 40 g of deionized water were mixed, heated and stirred at 70°C, and then 7 g of ammonium tetrathiomolybdate and 3 g of ammonium tetrathiotungstate were added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed with 70 g of pseudo-boehmite powder (60 wt% on dry basis), 30 g of pseudo-boehmite filter cake (25 wt% on dry basis), 0.5 g of zinc phosphate, 0.5 g of ammonium borate, 1 g of starch, 1 g of aluminum at 70°C. Sol, 1 gram of silica sol, 0.5 gram of magnesium carbonate, 0.5 gram of polymethyl methacrylate, 0.5 gram of ammonium oxalate and 1.5 gram of graphite were mixed, and then ultrasonically dispersed for 20 minutes, beaten, kneaded, and extruded into strips. Then, under nitrogen protection, the mixture was first dried with microwaves having a radiation frequency of 840 MHz, a microwave drying temperature of 100°C, and a drying time of 20 minutes, and then dried with microwaves having a radiation frequency of 2450 MHz, a microwave drying temperature of 400°C, and a drying time of 60 minutes to obtain a sulfided hydrodemetallization catalyst 3.

[0028] Embodiment 4:

[0029] 1.5 g of ammonium dithiocarbamate, 2.8 g of nickel acetate, 1 g of citric acid, 1 g of ethylene glycol and 40 g of deionized water were mixed, heated and stirred at 60° C., and then 3 g of ammonium tetrathiomolybdate and 7 g of ammonium tetrathiotungstate were added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed with 50 g of pseudo-boehmite powder (dry basis 70 wt%), 50 g of pseudo-boehmite filter cake (dry basis 20 wt%), 0.5 g of zinc phosphate, 0.5 g of ammonium borate, 1 g of starch, 1 g of aluminum solution at 60° C. The mixture was mixed with 1 gram of silica sol, 0.5 gram of magnesium carbonate, 6 grams of ammonium bicarbonate, 4 grams of polystyrene microspheres and 1 gram of conductive carbon black, and then ultrasonically dispersed for 20 minutes, beaten, kneaded and extruded into strips. Then, under nitrogen protection, the mixture was first dried with microwaves having a radiation frequency of 840 MHz, a microwave drying temperature of 110°C and a drying time of 25 minutes, and then dried with microwaves having a radiation frequency of 2450 MHz, a microwave drying temperature of 500°C and a drying time of 40 minutes to obtain a sulfurized hydrodemetallization catalyst 4.

[0030] Embodiment 5:

[0031] 2 g of ammonium dithiocarbamate, 2 g of nickel nitrate, 1 g of cobalt nitrate, 1 g of citric acid, 1 g of ethylene glycol and 40 g of deionized water were mixed, heated and stirred at 50° C., and then 10 g of ammonium tetrathiomolybdate was added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed with 60 g of pseudo-boehmite powder (65 wt% on dry basis), 40 g of pseudo-boehmite filter cake (23 wt% on dry basis), 0.5 g of zinc phosphate, 0.5 g of ammonium borate, 1 g of starch, and 1 g of aluminum sol at 50° C. , 1 gram of silica sol, 0.5 gram of magnesium carbonate, 2 grams of polymethyl methacrylate and 5 grams of carbon fiber sensitizer are mixed, and then ultrasonically dispersed for 30 minutes, beaten, kneaded, and extruded into strips. Then, under nitrogen protection, first dried with microwaves at a radiation frequency of 840 MHz, a microwave drying temperature of 120°C, and a drying time of 15 minutes, and then dried with microwaves at a radiation frequency of 2450 MHz, a microwave drying temperature of 350°C, and a drying time of 120 minutes to obtain a sulfide-type hydrodemetallization catalyst 5.

[0032] Comparative Example 1:

[0033] 2 grams of nickel nitrate, 1 gram of cobalt nitrate, 1 gram of citric acid and 40 grams of deionized water were mixed, stirred at 30°C for 1 hour, and then 10 grams of ammonium tetrathiomolybdate were added. The obtained sulfur-containing composite active metal precursor impregnation solution was mixed with 100 grams of pseudo-boehmite powder (68wt% on a dry basis) and 2 grams of aluminum sol at 30°C, and then pulped, kneaded, and extruded into strips. Then, under nitrogen protection, it was calcined at 500°C for 5 hours to obtain a hydrogenation demetallization catalyst A.

[0034] The physicochemical properties of the sulfided hydrodemetallization catalysts 1, 2, 3, 4 and 5 prepared by the present invention and the comparative example hydrodemetallization catalyst A are shown in Table 1.

[0035] Table 1 Physicochemical properties of hydrodemetallization catalysts

[0036] Catalyst No. 1 2 3 4 5 A <![CDATA[Specific surface area, m 2 / g]]> 236 242 256 237 245 182 Pore ​​volume, mL / g 0.59 0.55 0.58 0.57 0.56 0.32 Crushing strength, N / cm 195 189 192 186 197 140

[0037] The sulfided hydrodemetallization catalysts 1, 2, 3, 4 and 5 prepared by the present invention and the comparative hydrodemetallization catalyst A were respectively loaded into a fixed bed hydrogenation reactor, and the treated raw materials (see Table 2) were subjected to the following test conditions: reaction pressure of 12 MPa, hydrogen-to-oil volume ratio of 1200:1, volume space velocity of 1.5 h -1 , the reaction temperature is 380℃, the continuous operation is 5000 hours, and the impurity removal properties are shown in Table 2.

[0038] Table 2 Main properties of crude oil

[0039] project data <![CDATA[Density (20 °C), g / cm 3 > 0.972 Ni, μg / g 32.5 V, μg / g 82.6 Fe, μg / g 7.9 Ca, μg / g 8.7

[0040] Table 3 Evaluation results of catalysts

[0041] Catalyst No. 1 2 3 4 5 A Remove Ni+V, wt% 61.6 63.4 59.7 58.9 64.8 31.2 Fe removal, wt% 81.3 83.5 79.8 78.4 84.9 48.7 Ca removal, wt% 74.5 77.2 72.3 70.6 79.2 39.5

[0042] From the results in Table 3, it can be seen that the sulfided hydrodemetallization catalyst prepared by the method of the present invention has better Ni, V, Fe, Ca removal rates and good stability.

Claims

1. A method for preparing a sulfidation-type hydrodemetallization catalyst, It is characterized in that The preparation method comprises: firstly mixing ammonium dithiocarbamate, nickel salt and / or cobalt salt, citric acid, ethylene glycol and a certain amount of deionized water, heating and stirring, then adding ammonium tetrathiomolybdate and / or ammonium tetrathiotungstate, mixing the obtained sulfur-containing composite active metal precursor impregnation solution with 60-70wt% of pseudo-boehmite powder on a dry basis, 20-25wt% of pseudo-boehmite filter cake on a dry basis, zinc phosphate, ammonium borate, starch, aluminum sol, silica sol, magnesium carbonate, pore-forming agent at a temperature of 50°C to 90°C, and mixing the mixture with a mixture of 1% to 2% of the pseudo-boehmite powder on a dry basis, and mixing the mixture with 1% to 2% of the pseudo-boehmite filter cake on a dry basis, and mixing the mixture with ... filter cake on a dry basis, and mixing the mixture with 1% to 2% of the pseudo-boehmite powder on a dry basis, and mixing the mixture with 1% to 2% of the pseudo-boehmite filter cake on a dry basis, and mixing the mixture with 1% to 2% of the pseudo-boehmite filter cake on a dry basis, and mixing the mixture with 1% to 2% , a microwave sensitizer and a dispersant are mixed, and then ultrasonically dispersed, beaten, kneaded, and extruded into strips. Then, under nitrogen protection, microwave drying is first performed with a radiation frequency of 840 MHz and a microwave drying temperature of 100°C to 120°C, and then with a radiation frequency of 2450 MHz and a microwave drying temperature of 350°C to 600°C to obtain a sulfurized hydrogenation demetallization catalyst; the molar amount of the ammonium dithiocarbamate used is 50% to 300% of the molar amount of the nickel salt and / or the cobalt salt.

2. The method for preparing the sulfided hydrodemetallization catalyst according to claim 1, It is characterized in that The molar amount of the ammonium dithiocarbamate used is 100% to 150% of the molar amount of the nickel salt and / or the cobalt salt.

3. The method for preparing the sulfided hydrodemetallization catalyst according to claim 1, It is characterized in that The nickel salt and / or cobalt salt is selected from one or more of basic carbonate, nitrate and acetate.

4. The method for preparing the sulfided hydrodemetallization catalyst according to claim 1, It is characterized in that The pore-forming agent is one or more of ammonium carbonate, ammonium bicarbonate, urea, ammonium oxalate, polymethyl methacrylate and polystyrene microspheres, and the dosage is 1wt% to 20wt% of the weight of the carrier component.

5. The method for preparing the sulfided hydrodemetallization catalyst according to claim 1, It is characterized in that The microwave sensitizer is one or more of Fenton's reagent, activated carbon, graphite, conductive carbon black, semi-conductive carbon black and carbon fiber sensitizer.

6. The method for preparing the sulfided hydrodemetallization catalyst according to claim 1, It is characterized in that The ultrasonic time is 5 to 30 minutes.

7. The method for preparing the sulfided hydrodemetallization catalyst according to claim 1, It is characterized in that The 840 MHz microwave drying time is 10 to 30 minutes; the 2450 MHz microwave drying time is 20 to 120 minutes.

8. The method for preparing the sulfided hydrodemetallization catalyst according to claim 1, It is characterized in that The sulfided hydrodemetallization catalyst has a total nickel and / or cobalt content of 0.5wt% to 5wt% and a total molybdenum and / or tungsten content of 1wt% to 15wt% based on the weight of the final catalyst.

9. A sulfided hydrodemetallization catalyst prepared by the preparation method according to claims 1 to 8.

10. Use of the sulfurized hydrodemetallization catalyst according to claim 9 in the hydrogenation reaction of low-quality oil products with high sulfur, high nitrogen and high metal content.